On the relative importance of li bulk diffusivity and interface morphology in determining the stripped capacity of metallic anodes in solid-state batteries - Siniscalchi, M; Liu, J; Gibson, JS; Turrell, SJ; Aspinall, J; Weatherup, RS; Pasta, M; Speller, SC; Grovenor, CRM (American Chemical Society, 2022)
Lithium metal self-diffusion is too slow to sustain large current densities at the interface with a solid electrolyte, and the resulting formation of voids on stripping is a major limiting factor for the power density of solid-state cells. The enhanced morphological stability of some lithium alloy electrodes has prompted questions on the role of lithium diffusivity in these materials. Here, the lithium diffusivity in Li-Mg alloys is investigated by an isotope tracer method, revealing that the presence of magnesium slows down the diffusion of lithium. For large stripping currents the delithiation process is diffusion-limited, hence a lithium metal electrode yields a larger capacity than a Li-Mg electrode. However, at lower currents we explain the apparent contradiction that more lithium can be extracted from Li-Mg electrodes by showing that the alloy can maintain a more geometrically stable diffusion path to the solid electrolyte surface so that the effective lithium diffusivity is improved.